Remaking Muslim Lives: Everyday Islam in Postwar Bosnia and Herzegovina - Lived Islam: Colloquial Religion in a Cosmopolitan Tradition - Dzenita Karic (International Institute of Islamic Thought, 2021)
• Remaking Muslim Lives: Everyday Islam in Postwar Bosnia and Herzegovina (by David Henig)